Web literacy practices of teacher education students and in-service teachers in Greece : a descriptive study - Bougatzeli, Evangelia; Douka, Maria; Bekos, Nikolaos; Papadimitriou, Efi (Preschool and Primary Education, 2017)
In the expanding context of new literacies and multiliteracies, the abilities to know how to locate, to evaluate and to exploit Web information resources in order to construct knowledge, are acknowledged as extremely important worldwide. Current literacy curricula should encourage the development of such abilities, and their successful implementation requires teachers themselves to be properly prepared. The present study reports the web searching and evaluating practices for educational purposes employed by both pre-service and in-service teachers. Data was collected via an anonymous online questionnaire. The comparative study exhibis teachers’ web practices with the purpose of identifying aspects of web literacy that require attention when designing and implementing relevant educational initiatives. According to the research findings, both pre-service and in-service teachers are based almost exclusively on popular search engines to locate web information resources, and they choose such resources without examining their wider context. In order to evaluate web information resources, they consider mainly morphological and design elements, rather than content features such as their origin and credibility. The findings raise the potential of applying critical literacy principles on the Web so that teachers can approach it critiquely.[1] when using its resources in educational settings. [1] learn to think “critiquely” (a word coined by James Paul Gee), that is, not merely consume information but also “understand and critique systems of power and injustice in a world that [people] will see as simply economically inevitable" (Gee, 2000: 62).